Diverse Roles of Ethylene in Regulating Agronomic Traits in Rice - Yin, Cui-Cui (Front Plant Sci, 2017)
Gaseous hormone ethylene has diverse effects in various plant processes. These processes include seed germination, plant growth, senescence, fruit ripening, biotic and abiotic stresses responses, and many other aspects. The biosynthesis and signaling of ethylene have been extensively studied in model Arabidopsis in the past two decades. However, knowledge about the ethylene signaling mechanism in crops and roles of ethylene in regulation of crop agronomic traits are still limited. Our recent findings demonstrate that rice possesses both conserved and diverged mechanism for ethylene signaling compared with Arabidopsis. Here, we mainly focused on the recent advances in ethylene regulation of important agronomic traits. Of special emphasis is its impact on rice growth, flowering, grain filling, and grain size control. Similarly, the influence of ethylene on other relevant crops will be compared. Additionally, interactions of ethylene with other hormones will also be discussed in terms of crop growth and development. Increasing insights into the roles and mechanisms of ethylene in regulating agronomic traits will contribute to improvement of crop production through precise manipulation of ethylene actions in crops.